Critical Analysis of the Supportive and Suppressive Factors for the Children’s Literature Program in Malaysia - Siti Salina Mustakim; Ramlee Mustapha; Othman Lebar (Intelektual Pustaka Media Utama, 2015)
Literature in Education (LIE) is aimed at enhancing the pupils’ linguistic competence by providing an early beginning to a foundation in literature and literary works. In 2006, the literature component was introduced to pupils in Malaysian primary schools through two programs: Contemporary Children’s Literature (CCL) and Extensive Reading Program. The literature program is viewed as a vehicle to provide an early exposure to pupils on literary genres to enhance their understanding and appreciation of people’s cultures, values, and traditions. The primary aim of this study was to evaluate the provision of support, resources, training, and time allocation in the implementation of children’s literature among upper primary school teachers in Malaysia via the utilization of survey questionnaires, classroom observations and interviews. This study was conducted in a district in the state of Selangor. A sample of 56 upper primary school teachers from 19 schools were selected to answer the survey questionnaires. Interviews were conducted in one selected school in the District. The school was chosen based on the highest academic performance in the Malaysia Standard Examination for Primary Schools. Data were analyzed using SPSS version 19, and coded manually. Findings from survey indicated that 75% of the school management understand the objectives and goals of CCL in order to provide effective support to the program. Majority of the respondents (82%) agreed that the school management has allowed the English Language Department to manage its own expenses or resources for the program. Almost three-fourths (71.4%) of the respondents agreed that the provision of training and resources has produced capable and knowledgeable teachers to teach literature. However, the majority of the respondents (76.8%) disagreed that the time allocation provides sufficient time for them to fulfil the requirements of teaching two textbooks in a year. Interview data confirming the survey data reveal that the respondents were less satisfied with the time allocation to conduct their lesson for literature.